2019
DOI: 10.3390/agronomy9100576
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Best Management Practices in a Highly Anthropogenic and Ungauged Watershed Using the SWAT Model: A Case Study in the El Beal Watershed (Southeast Spain)

Abstract: Best management practices (BMPs) provide a feasible solution for non-point source pollution problems. High sediment and nutrient yields without retention control result in environmental deterioration of surrounding areas. In the present study, the soil and water assessment tool (SWAT) model was developed for El Beal watershed, an anthropogenic and ungauged basin located in the southeast of Spain that drains into a coastal lagoon of high environmental value. The effectiveness of five BMPs (contour planting, fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…High erosion class from the coverage of 53.61% in future scenarios was brought to 0%, 13.55%, 18.25%, 18.25%, 34.48% after recharge structure, filter strip of 6 m, contour farming, gully plugs, and two tillage operations, respectively. These percentage reductions are within the percentage reduction of sediment yield as obtained by a different researcher, such as 71% reduction by the implementation of contour farming (López-Ballesteros et al, 2019); up to 37.2% reduction with the recharge structure (Tuppad et al, 2011), 51% reduction by the gully plugs (Park et al, 2014); 5.4%-6.8% reduction in case of conservation tillage and zero tillage, respectively (Himanshu et al, 2019); 25% reduction by the application of filter strip (Parajuli et al, 2008).…”
Section: Evaluation Of Bmpssupporting
confidence: 75%
“…High erosion class from the coverage of 53.61% in future scenarios was brought to 0%, 13.55%, 18.25%, 18.25%, 34.48% after recharge structure, filter strip of 6 m, contour farming, gully plugs, and two tillage operations, respectively. These percentage reductions are within the percentage reduction of sediment yield as obtained by a different researcher, such as 71% reduction by the implementation of contour farming (López-Ballesteros et al, 2019); up to 37.2% reduction with the recharge structure (Tuppad et al, 2011), 51% reduction by the gully plugs (Park et al, 2014); 5.4%-6.8% reduction in case of conservation tillage and zero tillage, respectively (Himanshu et al, 2019); 25% reduction by the application of filter strip (Parajuli et al, 2008).…”
Section: Evaluation Of Bmpssupporting
confidence: 75%
“…In this context, watershed models are widely used for the long-term prediction of BMPs applications on the watershed. Several studies have shown that the Soil and Water Assessment Tool (SWAT) model is considered as a versatile model that integrates multiple processes which support effective watershed management across the globe [2,13,[25][26][27]. All of these studies indicated that the SWAT model is good enough to study the representation of agricultural BMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, several studies evaluated the effectiveness of BMPs to reduce sediment load and agricultural nutrients to freshwater ecosystems (e.g., Uniyal et al 2020;Briak et al 2019;Park et al 2014;Bosch et al 2013;Arabi et al 2008). However, majority of these studies were undertaken in North America (e.g., Lamba et al 2016;Bosch et al 2013;Arabi et al 2008), Europe (e.g., López-Ballesteros et al 2019;Engebretsen et al 2019;Lam et al 2011) and Asian continents (e.g., Uniyal et al 2020;Himanshu et al 2019;Park et al 2014). There are only few studies that evaluate BMPs in Africa (e.g., Briak et al 2019 in Morocco;Gathagu et al 2018 in Kenya; Betrie et al 2011 in Ethiopia).…”
Section: Introductionmentioning
confidence: 99%